2005
DOI: 10.1124/mol.105.016576
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Human Multidrug Resistance Protein 1 (ABCC1) by Matrix-Assisted Laser Desorption Ionization/Time of Flight Mass Spectrometry: Toward Identification of Leukotriene C4Binding Sites

Abstract: Multidrug resistance in tumor cells may be caused by reduced drug accumulation resulting from expression of one or more proteins belonging to the ATP-binding cassette (ABC) transporter superfamily. In addition to their drug efflux properties, certain ABC proteins such as multidrug resistance protein 1 (MRP1) (ABCC1) mediate the ATP-dependent transport of a broad array of organic anions. The intrinsically photoreactive glutathione-conjugated cysteinyl leukotriene C 4 (LTC 4 ) is a high-affinity physiological su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
(71 reference statements)
3
21
2
Order By: Relevance
“…Expression of BCRP in Pichia pastoris was carried out as previously described (Mao et al, 2004; Wu et al, 2005). Further details for expression and purification of BCRP are described in the Supplemental Data.…”
Section: Methodsmentioning
confidence: 99%
“…Expression of BCRP in Pichia pastoris was carried out as previously described (Mao et al, 2004; Wu et al, 2005). Further details for expression and purification of BCRP are described in the Supplemental Data.…”
Section: Methodsmentioning
confidence: 99%
“…A notable example is Lys 332 in the first TM of MSD1 (Fig. 1B) (43,50). Mutation of TM6 Lys 332 to an opposite, neutral, or even same-charge amino acid completely abrogates MRP1 binding of the high affinity physiological substrate LTC 4 , but has virtually no effect on the binding or transport of any OA substrate lacking a GSH moiety.…”
Section: Structural Determinants Of Solute Transport By Mrp1mentioning
confidence: 99%
“…The GSHdependent azidoagosterol A labeling of the protein was detected only in TMD2 [130], whereas the azido analogs of GSH and unconjugated drugs, such as rhodamine123, or quinoline, labeled both halves of MRP1, reacting with TMHs 10-11 in TMD1 and TMHs 16-17 in TMD2 [29,65,126]. The iodoarylazido analog of LTC 4 labeled the above two regions as well as TMH 12 [66], while the labeling with unmodified LTC 4 showed that the TMHs 6, 7, 10, and 17 are parts of the LTC 4 binding site [176].…”
Section: Handling Of Substratesmentioning
confidence: 99%